Pengaruh Level Energi Dalam Pakan Terhadap Kualitas Spermatozoa Ayam Kampung Secara Mikroskopis - Nining Haryuni; Anna Lidyawati; Binti Khopsoh; Niswatin Hasanah (Jurnal Ilmu Peternakan Terapan, 2020)
The purpose of this study was to determine the effect of energy levels in feed on the quality ofspermatozoa. The materials used in this study were 80 weeks old male native chickens, rations, 3%sodium chloride, eosin, and distilled water. This study used a Completely Randomized Design (CRD)consistied of 4 treatments and each treatment was repeated 4 times. Each repeatation was a malenative chicken. Collection of semen used the massage method on the abdominal area. The results ofthe study showed that the energy level in the rations increased (P<0.01) the mass motion anddecreased the motility of spermatozoa. The mean of mass motion scores obtained ranged 1.50% to3.00%, and the motility ranged 68.75% to 80.0%. The energy level in the rations increased(P<0.05) on the concentration and the number of live spermatozoa. The mean of concentrationobtained ranged 2.75x109 cells/ml to 3.75x109 cells/ml and the number of live spermatozoa ranged from 89.50% to 92.50%. Energy level in rations had no significant effect (P>0.05) on spermatozoaabnormality. The mean percentage of abnormal spermatozoa obtained ranged 2.27% to 2.38%.Based on this result, it can be concluded that the energy level in the rations could improve thequality of spermatozoa